2018
DOI: 10.1016/j.seizure.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

CHRNA4 variant causes paroxysmal kinesigenic dyskinesia and genetic epilepsy with febrile seizures plus?

Abstract: CHRNA4 may be a novel gene causing of PKD and GEFS+. Our study extends the genotypic-phenotypic spectrum of combined epileptic and dyskinetic syndromes, and provides a genetic linkage between PKD and GEFS+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…23,35 They are often associated with epilepsy, manifesting in patients with mutations in genes encoding synaptic proteins/receptors (PRRT2, CHRNA4), ion channels (KCNA1, KCNMA1, SCN8A, CACNA1A), and transporters (SLC2A1, SLC16A2, ATP1A2, ATP1A3). 167 Additionally, epilepsy occurs in tandem with paroxysmal non-kinesigenic dyskinesia in CACNA1A 168 and KCNMA1-related disease, [169][170][171] while paroxysmal exercise-induced dyskinesia is often described in cases of SLC2A1-related glucose transporter type 1 protein deficiency, 23 and more recently reported in patients with TBC1D24 mutations. In the context of epilepsy, paroxysmal kinesigenic dyskinesia is reported in patients harbouring mutations in PRRT2, 163,164 SCN8A, 31,33 SLC16A2, 165,166 and CHRNA4.…”
Section: Paroxysmal Dyskinesias and Epilepsymentioning
confidence: 99%
“…23,35 They are often associated with epilepsy, manifesting in patients with mutations in genes encoding synaptic proteins/receptors (PRRT2, CHRNA4), ion channels (KCNA1, KCNMA1, SCN8A, CACNA1A), and transporters (SLC2A1, SLC16A2, ATP1A2, ATP1A3). 167 Additionally, epilepsy occurs in tandem with paroxysmal non-kinesigenic dyskinesia in CACNA1A 168 and KCNMA1-related disease, [169][170][171] while paroxysmal exercise-induced dyskinesia is often described in cases of SLC2A1-related glucose transporter type 1 protein deficiency, 23 and more recently reported in patients with TBC1D24 mutations. In the context of epilepsy, paroxysmal kinesigenic dyskinesia is reported in patients harbouring mutations in PRRT2, 163,164 SCN8A, 31,33 SLC16A2, 165,166 and CHRNA4.…”
Section: Paroxysmal Dyskinesias and Epilepsymentioning
confidence: 99%
“…Recently, DEPDC5 S10 and CHRNA4 49 mutations have been associated with the syndrome of PKD plus epilepsy in single families. However, these two genes are also a cause of ADNFLE50 and it remains to be seen whether these episodes of paroxysmal dystonia are epileptic in nature or not.…”
Section: Disorders Presenting With Pxdmentioning
confidence: 99%
“…In terms of co-occurrence with epilepsy, patients with mutations in PRRT2 [9,12], SCN8A [13,14], SLC16A2 [15,16], and CHR-NA4 [17] have been reported in PKD (Fig. 1).…”
Section: Clinical Overviewmentioning
confidence: 99%
“…Recently, Jiang et al [17] found that co-occurrence of genetic epilepsy with febrile seizures plus and PKD have CHRNA4 mutations in PRRT2-negative families. Different seizure types were observed, including recurrent febrile seizures, which occurred between the ages of 3 and 7 years, afebrile seizures, including myoclonic seizures, which occurred between the ages of 6 and 11 years, and generalized tonic-clonic seizures, which occurred after the age of 14 years [17]. Symptoms of choreoathetosis and dystonia were mostly triggered by sudden movements and only occurred during daytime [17].…”
Section: Chrna4mentioning
confidence: 99%
See 1 more Smart Citation